CRIMINAL-LEGAL CHARACTERISTICS OF RECIDIVISM (American Journal of Research in Humanities and Social Sciences, 2026)
Recidivism represents one of the most complex and socially dangerous manifestations of multiple crimes within the criminal law of the Republic of Uzbekistan. It not only demonstrates the limited effectiveness of previous punitive and corrective measures but also significantly heightens the level of public danger and undermines public confidence in the justice system. This article offers a comprehensive analysis of the criminal-legal characteristics of recidivism, its conceptual foundations, mandatory features, types, and practical problems of qualification in accordance with the current legislation of the Republic of Uzbekistan. Particular emphasis is placed on the provisions of Article 34 of the Criminal Code of the Republic of Uzbekistan, which establishes a differentiated system comprising simple recidivism, dangerous recidivism, and especially dangerous recidivism. The study explores the close interrelation between recidivism and the institution of criminal record, the rules governing multiple crimes, the impact of recidivism on the individualization of punishment, and its role as an aggravating circumstance. Furthermore, the article addresses contemporary challenges in judicial practice, the balance between the principles of justice, humanism, and public protection, and the directions for further improvement of criminal-legal regulation in the context of the criminal policy of New Uzbekistan. Despite ongoing legislative reforms aimed at humanization, recidivism continues to pose serious theoretical and practical issues that require deep scientific understanding and effective law enforcement mechanisms.